2023
DOI: 10.1038/s41586-023-06560-0
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Biobank advances population and medical genomics of diverse ancestries

Mashaal Sohail,
María J. Palma-Martínez,
Amanda Y. Chong
et al.

Abstract: Latin America continues to be severely underrepresented in genomics research, and fine-scale genetic histories and complex trait architectures remain hidden owing to insufficient data1. To fill this gap, the Mexican Biobank project genotyped 6,057 individuals from 898 rural and urban localities across all 32 states in Mexico at a resolution of 1.8 million genome-wide markers with linked complex trait and disease information creating a valuable nationwide genotype–phenotype database. Here, using ancestry deconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Among the most important clinical associations are hypercholesterolemia, hyper triglyceridemia, body weight, creatinine levels, hypertension, and arthritis. Furthermore, this study confirmed earlier findings of the north–south gradient of European-Amerindian ancestry ( 44 ).…”
Section: Mexico’s Genetic Ancestry and Sociodemographic Backgroundsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the most important clinical associations are hypercholesterolemia, hyper triglyceridemia, body weight, creatinine levels, hypertension, and arthritis. Furthermore, this study confirmed earlier findings of the north–south gradient of European-Amerindian ancestry ( 44 ).…”
Section: Mexico’s Genetic Ancestry and Sociodemographic Backgroundsupporting
confidence: 92%
“…As shown in this review, within LATAM, despite having a common social history of the peopling of the continent, a wide spectrum of ancestral inter-variability is notable as well a distinct environmental conditions ( 24 , 25 , 28 , 33 ). In the case of Mexico, it has been shown that the North–South gradient of the European-Amerindian ancestry impacts importantly in the distribution of the several genes with biomedical implications for the risk of chronic liver diseases ( Tables 2 , 3 ; Figure 3 ) ( 32 , 44 , 45 , 153 ). More so, this pattern of distribution could also be replicated intra-regionally in light of the social-demographic movements that occurred over time as in the case of the ABCA1 polymorphism ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the incidence of childhood ALL varies across different Hispanic/Latino populations and appears to correlate with genetic ancestry, with reported incidences being higher in countries where the populations have relatively high IAM ancestry proportions, such as Mexico and Ecuador, but lower in countries such as Argentina where the population has a larger European ancestral component. 37 , 38 , 39 , 40 Similarly, the incidence of childhood ALL in Puerto Rico, where the population has relatively high proportions of European and African ancestry but much less IAM ancestry, is lower than in Hispanic/Latino children in the contiguous US. 41 , 42 The majority of Hispanic/Latino patients with ALL in our California-based study would have origins in Mexico and other Central American countries ( Table S1 ) and thus, on average, have higher proportions of IAM ancestry compared to Hispanic/Latino patients of, for example, Puerto Rican or Cuban origin.…”
Section: Discussionmentioning
confidence: 99%
“…The IKZF1 variants likely contribute significantly to the increased ALL risk in Hispanic/Latino individuals both in the US and in Latin America, with some of the highest global rates of childhood ALL reported in Mexico City. 37 , 43 Efforts are underway to understand the genetic diversity that exists across Indigenous American subpopulations, 39 , 40 and it will be important to elucidate how different Indigenous American ancestries influence allele frequencies and effect sizes at IKZF1 and other ALL risk loci for future precision prevention efforts to alleviate the disparity in ALL incidence in Hispanic/Latino individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although at different computing costs between t-SNE and UMAP, both techniques integrating principal components of genotype data were previously applied to large datasets (e.g., [Diaz-Papkovich et al, 2020]), providing a more comprehensive view of inferring population genetic structure in plants (Fu et al, 2022; Ma et al, 2021), invertebrates ( Anopheles gambiae 1000 Genomes Consortium, 2020; Schmidt et al, 2020, 2021; Simon et al, 2021), and extensively in humans (Černý et al, 2023; Chyleński et al, 2019; Diaz-Papkovich et al, 2019; Halldorsson et al, 2022; Margaryan et al, 2020; Sengupta et al, 2021; Sohail et al, 2023). Interestingly, despite being available for several years, t-SNE and UMAP have not been widely adopted in population genomics research for non-human vertebrates.…”
Section: Introductionmentioning
confidence: 99%